The Impact of Nurse Characteristics and Work Productivity on Patient Satisfaction: A Systematic Review - Sofiatun, Sofiatun; Fitryasari, Rizki; Ahsan, Ahsan (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The quality of nursing care was an important value that can affect the quality of the hospital. Purpose: This systematic review was to analyze the relationship between nurse characteristics to work productivity of nurses and what is the impact on patient satisfaction. The research design was a systematic review by the PRISMA approach. The criteria inclusion were nurses who worked in hospitals. Selection of the journals was carried out using: 1) Scopus, PubMed, Springer Link, and Science Direct database, 2) Searches on January 19th-28th 2021, 3) 2015-2021 journals published in English, 4) used the PICOS approach to analyzing. The analysis resulted in 1.544 journals and 15 appropriate were selected. Nurse characteristics were related to the work productivity of nurses. The motivation was the characteristic of nurses that most influences to work productivity of nurses.